2021
DOI: 10.3390/cryst11091053
|View full text |Cite
|
Sign up to set email alerts
|

Optically Rewritable Liquid Crystal Displays: Characteristics and Performance

Abstract: Recent achievements in the photoalignment technique for fabrication of optically rewritable electronic paper with high performance characteristics are surveyed with emphasis on temporal constraints on the exposure process. The possibility of creating electrode-free electronic paper has very important practical aspects. However, many existing studies do not include sufficient analysis on how to achieve acceptable reflective characteristics within short exposure time. In order to achieve this goal, we have appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Thus, optically rewritable electronic paper (ORW e-paper) is an electrode-free and optically addressed device with a grayscale capability, wide viewing angles and a contrast ratio of about 10:1. All these properties have been widely discussed in our previous reviews [7,8] and studies [9,10]. Further investigation of ORW e-paper has shown that it can play the role as an element base for advanced light-driven applications, which include security films [11], methods of 3D visualization [12,13], color reflectors [14] and transparent devices [15].…”
Section: Introductionmentioning
confidence: 95%
“…Thus, optically rewritable electronic paper (ORW e-paper) is an electrode-free and optically addressed device with a grayscale capability, wide viewing angles and a contrast ratio of about 10:1. All these properties have been widely discussed in our previous reviews [7,8] and studies [9,10]. Further investigation of ORW e-paper has shown that it can play the role as an element base for advanced light-driven applications, which include security films [11], methods of 3D visualization [12,13], color reflectors [14] and transparent devices [15].…”
Section: Introductionmentioning
confidence: 95%